Negotiating boundaries: Encyclopédie, romanticism, and the construction of science - Marcelo Fetz (História, Ciências, Saúde: Manguinhos)
Abstract Natural history in the eighteenth and nineteenth centuries has been widely debated in the field of the social sciences. This paper explores the social negotiation of boundaries in the Encyclopédie and romantic science. Highlighting the importance of imagination and aesthetics to the scientific realms, we perceive a different comprehension of the scientific field through the empirical study of how scientific demarcation is constructed. Works by Erasmus Darwin, Goethe, and Humboldt illustrate how reliable science was performed through atypical scientific methods. After pointing out the links between literary, artistic, and scientific works, we then debate a series of changes that framed the scientific imagery of romantic and encyclopaedic sciences.